Chemical Constituents of Glycosmis Crassifolia and G. Chlorosperma (Rutaceae) and Their Biological Activities - Nafiah, Mohd Azlan (2001)
The phytochemical study on Glycosmis crassifolia (limau hutan) and G. chlorosperma (Rutaceae) involves extraction and separation by using various chromatographic methods, structural determination by spectroscopic techniques such as IR, NMR including 2D-NMR and MS. The structure of the compounds were elucidated by comparison with the previous works. Isolation work on roots of G. crassifolia yielded maculocidine (44). From the leaves, two more compounds were isolated and the structure elucidated. One of them was identified as a new alkaloid, glycofuranoxine (45) and the other one was stigmata-3,5,22-trien-3-01 (46). Further study on the twigs of the same plant afforded two known compounds including ergosta-4,6-dien-3-01 (47) and stigmata-5-en-3-01 (48). Detail study on the leaves extract of Glycosmis chlorosperma yielded two compounds. One of them was identified as a new compound, 5-hydroxy-7,4'dimethoxy- 8-(-3"-methylbut-2"-enyl)f1avanone (49) and the other one was known as dambullin (50). Crude extract from various plant were screened for antifungal activity using poison food method against Sclerotium rolfsii. However, the petroleumether, chloroform and methanol extract of the roots, leaves and twigs of the plant failed to show any activity in inhibition of mycelial growth and sclerotial germination.